Short term low-calorie diet improves insulin sensitivity and metabolic parameters in obese women - Grazielle Vilas Bôas Huguenin; Sofia Kimi Uehara; José Firmino Nogueira Netto; Egberto Gaspar de Moura; Glorimar Rosa; Magna Cottini da Fonseca Passos (Nutrición Hospitalaria, 2014)
Obesity and insulin resistance are associated with an increase of cardiovascular risk factors, including adipocytokines. The aim of this study was to investigate the effect of low-calorie diet on serum lipids, adipokines, insulin resistance and body composition in obese women. It was a clinical trial with class I obese women aged 30-45 years submitted to hypocaloric diet for 90 days. Dietary intake, anthropometric parameters, body composition, serum lipids, glucose, insulin, leptin, adiponectin, HOMA-IR and QUICKI indexes were evaluated at the baseline, 30, 60 and 90 days. There was 30% significant decrease in energy intake, and also decrease in body weight, body mass index and waist circumference (p < 0.01) throughout the treatment period. Despite the amount of lean body mass (kg) reduced in average, it was observed that lean body mass (%) had increased (p < 0.01) and that the amount of fat body mass (kg) had decreased significantly in the third month (p < 0.05). Systolic blood pressure reduced up to -5mmHg (p < 0.05) after 90 days. Was observed a decrease (p < 0.05) on serum insulin and HOMA-IR until the 60th day, while the serum adiponectin increased (p < 0.01) during treatment. Corroborating with the reduction of fat body mass and weight, serum leptin also reduced (p < 0.01). These results suggest that the short-term low-calorie diet reduces total body fat, mainly found in the abdominal region, and efficiently improve insulin sensitivity decreasing cardiovascular risk in obese women.